Penegakkan Hukum Pidana terhadap Pelaku Kekerasan dalam Rumah Tangga terhadap Perempuan dan Anak di Indonesia - Fery Singgih Ardianto; Parasian Simanungkalit; Anwar Sadat (Syntax Corporation, 2023)
Violence against women is a crime that has received much attention from social scientists in recent years. From the data collected, it is not known exactly how many women, in this case, wives are victims of violence, ranging from reluctance to provide for their wives to sexual violence. Therefore, to overcome the problem of violence against women in the household, there needs to be joint action between all parties, both from the community to the apparatus and legislation that functions properly so that the problem of violence in Indonesia such as the problem of violence can be overcome properly. In its current development, victims of domestic violence find it difficult to submit their suffering to law enforcement, because of the strong view that the harsh treatment of husbands to wives is part of private events (domestic affairs) so that it cannot be reported to the police. So that the suffering of victims of domestic violence (wives) is prolonged without protection. The condition of victims of such domestic violence is still dilemmatic after the promulgation of Law Number 23 of 2004 concerning the Elimination of Domestic Violence. Because if a wife who experiences domestic violence reports her husband to the police, it is feared that the husband will be more violent towards him after the wife returns home because there is no legal protection from the police and / or court. There are even some wives who are victims of domestic violence who prefer to endure the suffering of violence because they feel worried about their future if their husbands deal with law enforcement.